Do Status discrepancy and socioeconomic immobility really drive compensatory consumption?. (September 2020) - Kim, Heewon; Jang, SooCheong (Shawn)
Highlights: This study explored impulsive consumption in the hospitality industry as a form of compensatory behavior rising from negative self-evaluations. Self-evaluations have been operationalized as status discrepancy and perceived socioeconomic immobility in this study. Results showed that satisfactory self-assessments, rather than status discrepancy or socioeconomic immobility, lead to impulsive consumption. This study could also verify that participants jointly reflect status discrepancy and socioeconomic immobility in consumption contexts. Moreover, millennials were more sensitive than older generations towards mobility information. Abstract: This research aimed to empirically explore whether impulsive consumption in the hospitality industry could be explained as a form of compensatory behavior that individuals engage in to cope with pessimistic self-evaluations. In this study, these self-evaluations have been operationalized as status discrepancy and perceived socioeconomic immobility. To test the hypotheses, this study used a three-way factorial design in two consumption settings: (1) leisure activities and (2) restaurant visits. Across the two studies, the results indicated that satisfactory self-assessments, rather than status discrepancy or socioeconomic immobility, lead to impulsive consumption. Despite the reversed findings, this study verified that participants jointly reflect status discrepancy and socioeconomic immobility in consumption contexts. Moreover, the findings suggest that millennials are more sensitive towards mobility information than older generations. This study sheds light on generational differences in impulsive consumption in the hospitality industry.